(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
The results of this study concluded that, the offensive and defensive strategy had run quite well seen from the indicators of the offensive strategy which included: (1) the approach of this coworker was quite good and must be improved again seen from the presence of some employees who reprimand when other employees who broke the rules (2) of the familial approach was already quite good and must be improved again regarding conducting weekly evaluations for the section head and its members. While the defensive strategy which included: (1) light sanctions themselves had run well, with sanctions in the form of written warnings for employees who commit violations, for example: not coming to the office for 6 to 10 days (2) moderating sanctions had also run well if there was an employee who did pathology which required him to be given a moderate sanction (3) severe sanctions had gone well as well as moderate sanctions if there were employees who carried out pathology which required him to be given severe sanctions without having to be heavy-hearted to employees who broke the rules. Keywords: strategy, pathology